2016
DOI: 10.1016/j.jcyt.2015.10.008
|View full text |Cite
|
Sign up to set email alerts
|

The current landscape of the mesenchymal stromal cell secretome: A new paradigm for cell-free regeneration

Abstract: The unique properties of mesenchymal stromal/stem cells (MSCs) to self-renew and their multipotentiality have rendered them attractive to researchers and clinicians. In addition to the differentiation potential, the broad repertoire of secreted trophic factors (cytokines) exhibiting diverse functions such as immunomodulation, anti-inflammatory activity, angiogenesis and anti-apoptotic, commonly referred to as the MSC secretome, has gained immense attention in the past few years. There is enough evidence to sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
283
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 371 publications
(296 citation statements)
references
References 82 publications
3
283
0
2
Order By: Relevance
“…Considering that exosome-like vesicles are completely cell-free and not highly immunogenic, exosome-like vesicles could be an important tool for use during adipose tissue engineering (Konala et al, 2016). Therefore, further research is needed to study the possibility that exosome-like vesicles act as a proadipogenic factor to enable use during adipose tissue engineering.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that exosome-like vesicles are completely cell-free and not highly immunogenic, exosome-like vesicles could be an important tool for use during adipose tissue engineering (Konala et al, 2016). Therefore, further research is needed to study the possibility that exosome-like vesicles act as a proadipogenic factor to enable use during adipose tissue engineering.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence that extracellular vesicles (EVs) released by MSCs contribute to the therapeutic repertoire of the trophic factors of MSCs [66,67]. Application of MSC-derived EVs has shown efficacy in various animal models such as myocardial infarction, limb ischemia, wound healing, or kidney, liver and lung injury [68,69].…”
Section: Mscs Secrete Trophic Factors and Produce Extracellular Vesiclesmentioning
confidence: 99%
“…Studies have revealed many functions mediated by this type of cell, such as reducing inflammation, modulating immune responses, promoting tissue regeneration, and inhibiting tumor progression [7][8][9]. In addition, MSC treatment has been the focus of more than 560 clinical trials that supply exogenous or activate endogenous MSCs [10] and has become the most effective source of cell-based therapy [11,12]. Human umbilical cord MSCs (uMSCs) are a kind of MSC derived from umbilical cord through a noninvasive procedure, allowing robust in vitro culture expansion, and its physiological properties could be basically reserved under cryostorage [13][14][15].…”
Section: Introductionmentioning
confidence: 99%